Will immunotherapy lead to a breakthrough in the treatment of older adults with ALL?. Issue 4 (December 2021) - Aldoss, Ibrahim; Advani, Anjali; Pullarkat, Vinod
Abstract: Historically, older adults with B-cell acute lymphoblastic leukemia (ALL) have done poorly with chemotherapy-based treatment. Therefore, new innovative approaches are urgently needed to improve outcomes for this population. CD19-targeted immunotherapies such as blinatumomab and chimeric antigen receptor (CAR) T cell therapy have produced remarkable responses in relapsed/refractory (r/r) B-cell ALL, including clearance of minimal residual disease (MRD). Available data support the efficacy and safety of blinatumomab in older adults with advanced B-cell ALL. Therefore, its application is being extended to frontline regimens for B-cell ALL, particularly in older adults. There are several studies actively examining the role of blinatumomab alone or in combination with attenuated dosing of conventional chemotherapy or novel agents in older adults with newly diagnosed ALL and early data are encouraging. While CD19-targeted CAR (CD19CAR) T cell therapy is active in children and young adults with r/r B-cell ALL, data supporting its efficacy and safety in older adults with ALL is scarce. Furthermore, the commercially FDA approved CD19CAR T cell therapy product for r/r ALL is restricted only to patients ≤25 years of age. Although there are concerns about older adults tolerating the expected toxicities associated with CAR T cell therapy, which may be life threatening, tailored approaches for prophylactic and pre-emptive interventions combined with utilization of safer CAR T cell platforms may improve tolerability and further extend the use of this promising treatment to older patients with ALL. In this review, we will discuss the progress in immunotherapies for older adults with B-cell ALL and their potential for transforming frontline therapy for newly diagnosed patients.